Mechanically robust honeycomb graphene aerogel multifunctional polymer composites. (November 2015) - Zhang, Qiangqiang; Xu, Xiang; Li, Hui; Xiong, Guoping; Hu, Han; Fisher, Timothy S.
Abstract: This work reports the fabrication and characterization of three-dimensional (3D) graphene aerogel (GA)–polydimethylsiloxane (PDMS) composites (GAPC) with outstanding mechanical, electrical and thermal properties. GAPC was fabricated by impregnating 3D GA frameworks with PDMS via ice-bath-assisted infiltration and vacuum curing processes. Because of the well-interconnected 3D GA frameworks, GAPC exhibits extremely large deformability (compressive strain = 80% and tensile strain = 90%), high electrical and thermal conductivities (1 S/cm and 0.68 W/(m K), respectively), a stable piezo-resistance effect, rapid electric Joule heating performance (( dT / dt )max  > 3 °C/s under a heating power of 12 W/cm 3 ), and high hydrophobicity (contact angle = 135°). Furthermore, GAPC exhibits a negative temperature coefficient of expansion with decreased electrical resistivity over a broad temperature range, indicating a typical semiconducting behavior and a dual two-dimensional/3D hopping conduction mechanism.